Association between nutritional intake, physical activity, and gestational weight gain in overweight pregnant women: a cross-sectional study - Ayu Rahadiyanti; Fillah Fithra Dieny; Nurmasari Widyastuti; Dewi Marfu'ah Kurniawati; Choirun Nissa; Putri Tiara Rosha (AcTion: Aceh Nutrition Journal, 2025)
Excessive weight gain during pregnancy is a risk factor, which can be modified to prevent pregnancy and postpartum complications. Gestational weight gain (GWG) is also influenced by the regulation of nutritional intake and physical activity, especially during the COVID-19 pandemic. This study aimed to analyze the relationship between nutritional intake and physical activity in overweight pregnant women with gestational weight gain. This cross-sectional study was conducted in May and November 2022. A total of 66 overweight/obese pregnant women aged 20 – 40 years at the Public Health Center in Semarang were recruited using a consecutive sampling technique. Data were collected using interviews, questionnaires, and anthropometric measurements.  Data analysis was performed using the Pearson’s correlation, Spearman’s correlation, and linear regression. Pregnant women who were overweight or obese gained an average of 0,42 kg of weight each week, with the bulk of this gain deemed improper (68,2%). Parity (p=0,011; r=-0,309) and sufficient protein consumption (p=0,031; r=-0,266) were associated with GWG. The conclusion is that there will be less weight gain during pregnancy if the protein intake is high.